Knowledge, attitude, and practice toward azithromycin infusion reactions among pediatric nurses: a cross-sectional study - Linlin Wei; Jianying Xu; Chaolang Zhang; Cuiying Chen; Jia Chen (BMC Nursing)
Abstract Background Infusion-related adverse reactions to azithromycin, though uncommon, can pose serious risks in pediatric care, warranting focused attention from nursing professionals. Pediatric nurses are key to early identification and intervention, but their knowledge, attitude, and practice (KAP) regarding such events remain unclear. Methods We conducted a cross-sectional survey among 835 pediatric nurses from 53 hospitals in Zhejiang Province, China. A custom-designed, expert-reviewed questionnaire assessed demographic characteristics, azithromycin-related knowledge, attitudes, and practices. Confirmatory factor analysis (CFA) and reliability testing (Cronbach’s alpha) were used to evaluate the instrument’s validity. Mediation analysis was performed to examine the indirect effects of knowledge and job satisfaction on practice, with attitude as a mediator. Results The CFA indicated acceptable model fit (RMSEA = 0.043; CFI = 0.892), and internal consistency was moderate to good across domains (α = 0.637–0.84). Nurses demonstrated moderate knowledge (mean score 13.59/20), constructive attitudes (28.43/35), and high levels of self-reported practice (42.30/50). Job satisfaction and 5–8 years of experience were associated with better attitudes and practices. Mediation analysis revealed that knowledge (β = 0.11, P = 0.034) and job satisfaction (β = 0.49, P < 0.001) directly influenced attitude, which in turn mediated their effects on practice. Knowledge had only an indirect effect on practice (β = 0.04, P = 0.042), underscoring the importance of attitudinal reinforcement. Conclusions Pediatric nurses possess limited pharmacological knowledge but exhibit safe infusion practices, likely driven by standard protocols and clinical experience. Educational interventions should go beyond factual training to include attitude-shaping strategies. Hospitals should prioritize structured in-service programs, simulation-based learning, and pre-infusion checklists to enhance safety. Future large-scale, multi-center, and longitudinal studies across diverse regions are warranted to validate these findings and enhance their generalizability. Clinical trial number Not applicable.